2015
DOI: 10.1007/s00704-015-1537-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of blowing dust events in the Taklimakan Desert

Abstract: The Taklimakan Desert is the source of most blowing dust events in China. However, previous studies of sandstorms in this region have not included data from the inner desert because of the difficulty in making observations in this area. In this study, the spatial and temporal variations of blowing dust events, including sandstorms and blowing sand, and its relations with climatic parameters in the Taklimakan Desert were analyzed using data from ten desert-edge meteorological stations during 1961 to 2010 and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Statistics from 20 dust storms in Hotan Prefecture are consistent with a "sharp increase followed by a slow decrease". Previous research by Yang et al (2016) suggested that variations in dust events are mainly affected by strong winds and daily temperatures with correlation coefficients of 0.46 and -0.41 for dust events respectively across the whole Taklimakan Desert. This correlation analysis indicates that a strong wind is the dominant factor that results in the formation of sand-dust storms.…”
Section: Variations In Hourly Mean Pm 10 Concentrations In Hotan Prefmentioning
confidence: 95%
“…Statistics from 20 dust storms in Hotan Prefecture are consistent with a "sharp increase followed by a slow decrease". Previous research by Yang et al (2016) suggested that variations in dust events are mainly affected by strong winds and daily temperatures with correlation coefficients of 0.46 and -0.41 for dust events respectively across the whole Taklimakan Desert. This correlation analysis indicates that a strong wind is the dominant factor that results in the formation of sand-dust storms.…”
Section: Variations In Hourly Mean Pm 10 Concentrations In Hotan Prefmentioning
confidence: 95%
“…Other researchers have highlighted a trend towards greater vegetation cover in northern China generally in recent decades but primarily due to greater rainfall and warmer temperatures [72,73]. In the Taklamakan Desert, where Yang et al [74] identified a declining trend in sandstorms from 1961 to 2010 and a similar trend in blowing sand and dust after 1979, these authors state that "there is no obvious effect of human activities on the decrease in the number of blowing dust events during the last 50 years. "…”
Section: Northeast Asia: Minqin Chinamentioning
confidence: 99%
“…Wang et al [38] also pointed out that the glacial retreat and snow melting in the Tibetan Plateau are closely related to the transmission of dust particles. Earlier studies on dust in the TD mainly relied on the data of meteorological stations to analyze the frequency of dust occurrence [39,40]. The vertical distribution characteristics of dust aerosols were often studied by means of satellite remote sensing, such as CALIPSO, moderate-resolution imaging spectroradiometer (MODIS) and simulation results [41][42][43].…”
Section: Study Areasmentioning
confidence: 99%